A relação entre a evidenciação de informações nos pareceres de auditoria e o valor das ações de companhias abertas listadas na Bovespa - Jacques, Flávia Verônica Silva (Universidade do Vale do Rio dos Sinos, 2011)
The disclosure of information, according to agency theory perspective, is presented as a way to reduce information asymmetry among economic agents in the market. However, some disadvantages are pointed out by the theory of cost of owner by the costs resulting from disclosure of private information, including: the costs of production and dissemination and the costs arising from the use of information by competitors. In this context, the research investigates the use of audit opinion by investors as an aid to decision making. These research evidence on the relationship between information highlighted in the audit opinions of companies and the variation of the average value of its shares on the market. The study population consists of 211 publicly held companies and non-financial publicly traded in its traditional market, for the years ended 2005, 2006, 2007, 2008 and 2009. Whereas many of these companies were not listed throughout this period, also had no opinions with caveats, were excluded 178 companies, setting a final sample of 33 (thirty three) companies. This study is characterized by content analysis, at first, held in Disclosure of audit opinions. Through content analysis, we elaborated a list of indicators of information highlighted. As a result, we created categories of indicators for the development of statistical analysis. The results revealed that the indicator of disclosure of accounting practices has a positive explanatory coefficient of variation of the average value of the shares, which comes to meet the assumptions of agency theory.
Keywords: Parecer de auditoria; Teoria de agência; Teoria de custo do proprietário; Disclosure; Audit report; Agency theory; Cost theory of the owner; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis